Energy transfer processes in organic molecular semiconductors - Eggimann, H (2020)
Organic semiconductors exhibit excellently suited material properties for a variety of applications and offer the possibility of low-cost and large-scale production. This thesis analyses photonic properties of several organic semiconductors, which are of great interest for different applications. To explore these materials, a combination of steady-state and time-resolved optical measurement techniques is employed and energy transfer dynamics within organic semiconductors are modelled. Research was focused on the following areas: